USE OF PSYCHOACTIVE SUBSTANCES IN THE REGIONAL METHADONE CENTER IN SERBIA - Popović, Tamara; Dickov, Aleksandra; Knežević, Vladimir; Ivanović Kovačević, Svetlana; Nikolić, Božana (HEALTH CARE, 2024)
Introduction: Patients on methadone maintenance therapy often use psychoactive substances (nicotine, alcohol, cannabis, cocaine, amphetamine-type stimulants, sedatives, hypnotics, hallucinogens and others), which can negatively affect therapeutic outcomes. The aim of this study was to determine the prevalence and pattern of psychoactive substance use among patients on methadone maintenance therapy. Methods: The study was conducted in the Methadone Center of the University Clinical Center of Vojvodina in the period August-October 2022. Data were collected through general and ASSIST (The Alcohol, Smoking and Substance Involvement Screening Test) questionnaires. Descriptive statistics was used to analyze the collected data. Results: In total, 60 patients on methadone maintenance therapy were included in the study. Among them, the prevalence of the use of nicotine, alcohol and illicit psychoactive substances was 98.3%, 10% and 5.1%, respectively, in the last 3 months preceding the investigation. The use of illicit psychoactive substances was mostly occasional. Three patients had ASSIST score >27 which was associated with a high risk of developing dependence to alcohol (two patients) or cannabis (1 patient). Conclusion: The study indicated a significant difference in the prevalence of the use of licit and illicit psychoactive substances. Therefore, their use should be monitored through regular and occasional urinalysis.